Tindak Tutur dan Kesantunan Berbahasa dalam Perspektif Pragmatik - Ade Surya Anugrah Putra; Mohd. Dzaky Ekri; Reza Fahlevi Ahyat; Silvina Noviyanti, S.Pd., M.Pd. (STKIP Subang, 2025)
This study aims to examine speech acts and language politeness from a pragmatic perspective through a library research approach. The focus of the study includes identifying types of speech acts, the politeness strategies employed by speakers, and the relationship between the two across various communication contexts. The research data were obtained from relevant books, journals, proceedings, and scholarly works. The analysis shows that speech acts—whether assertive, directive, expressive, commissive, or declarative—carry different levels of potential threat to the hearer’s face, thus requiring the use of specific politeness strategies. Positive and negative politeness strategies were found to play an essential role in maintaining social relationships, reducing illocutionary force threats, and aligning speech with cultural norms. This study also highlights a research gap in the comprehensive integration of speech act analysis and politeness strategies. The findings are expected to contribute theoretically to the development of pragmatics and serve as a reference for future empirical research. Keywords: Speech Acts, Language Politeness, Pragmatics